Dampak CR, DER dan NPM terhadap Tobin`s Perusahaan Sub Sektor Kosmetik dan Barang Keperluan Rumah Tangga yang terdaftar di BEI - Debi Eka Putri; Eka Purnama Sari (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The purpose oft his study is to look at and analyze the effect of CR, DER, NPM on Tobin's Q together and individually in theCosmetics and Household Utilization Sub-sector Companies Listed on the IDX. The approach used is an associative approach. This type of data uses quantitative data. All Cosmetics and Household Goods Sub-sector companies registered on the IDX are used for this population while the sample that meets the criteria with purposive sampling techniqueis 4 companies for 8 years of research. Data collection techniques using documentation. Techniques for analyzing data use multiple linear regression, correlation, R-Square also hypothesis testing. The results prove simultaneously that CR, DER, NPM have a significant effect on Tobin's Q. Partially CR has an insignificant positive effect on Tobin's Q, while DER and NPM have a significant positive effect on Tobin's Q.